Consumer law and consumerism: a sistematic literature review on the field of teaching (Revista Contexto & Educação, 2023)
The main objective of this paper is to map out the knowledge already developed concerning academic and scientific production related to the teaching of Consumer Law and Consumerism. This is a systematic review based on the state of the art that used the database from the CAPES Thesis and Dissertations Catalog. First, the methodological path for selecting the studies that constituted the final sample was described, meeting the inclusion criteria. After that, in order to facilitate the analysis and discussion of the results, the topics surveyed were categorized into three axes, of the themes more focused on: Consumer Law; Consumption / Consumerism; and Financial Education. The predominant methodological approaches and the authors most frequently mentioned in the studies were analyzed, in addition to having the objectives and results of the research been pointed out. Finally, it was concluded that the scientific production concerning the teaching of Consumer Law is quite scarce, and that its approach in an integrated way with the themes of Consumerism and Financial Education may prove to be a valid strategy for the teaching of the theme to get closer to the students’ reality, materializing in concrete actions and promoting citizenship through the realization of consumer rights.
Keywords: Consumer Law. Consumerism. Financial Education. Teaching.